Heterogeneity of Ryanodine Receptor Dysfunction in a Mouse Model Of Catecholaminergic Polymorphic Ventricular Tachycardia - Loaiza, Randall (2012)
RATIONALE: Most cardiac ryanodine receptor (RyR2) mutations associated with Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT) are postulated to cause one distinctive form of Ca(2+) release dysfunction. Considering the spread distribution of CPVT mutations, we hypothesized that dysfunctional heterogeneity was also feasible. OBJECTIVE: To determine the molecular and cellular mechanism(s) by which a novel RyR2-V2475F mutation associated with CPVT in humans triggers Ca(2+)-dependent arrhythmias in whole hearts and intact mice. METHODS AND RESULTS: Recombinant channels harboring CPVT-linked RyR2 mutations were functionally characterized using [(3)H]ryanodine binding and single channel recordings. Homologous recombination was used to generate a knock-in mouse bearing the RyR2-V2475F mutation. Ventricular myocytes from mice heterozygous for the mutation (RyR2-V2475F(+/−)) and their wild-type (WT) littermates were Ca(2+)-imaged by confocal microscopy under conditions that mimic stress. The propensity of WT and RyR2-V2475F(+/−) mice to develop arrhythmias was tested at the whole heart level and in intact animals. Recombinant RyR2-V2475F channels displayed a) increased cytosolic Ca(2+) activation, b) abnormal PKA phosphorylation, and c) increased activation by luminal Ca(2+). The RyR2-V2475F mutation appears embryonic lethal in homozygous mice, but heterozygous mice have no alterations at baseline. Spontaneous Ca(2+) release (SCR) events were more frequent and had shorter latency in isoproterenol-stimulated cardiomyocytes from RyR2-V2475F(+/−) hearts, but their threshold was unchanged with respect to WT. Adrenergically-triggered tachyarrhythmias were more frequent in RyR2-V2475F(+/−) mice. CONCLUSIONS: The mutation RyR2-V2475F is phenotypically strong among other CPVT mutations and produces heterogeneous mechanisms of RyR2 dysfunction. In living mice, this mutation appears too severe to be harbored in all RyR2 channels, but remains undetected under basal conditions if expressed at relatively low levels. β-adrenergic stimulation breaks the delicate Ca(2+) equilibrium of RyR2-V2475F(+/−) hearts and triggers life-threatening arrhythmias.